2014
DOI: 10.1213/ane.0000000000000042
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Lysis of Adhesions for Failed Back Surgery and Spinal Stenosis

Abstract: Considering our modest success rate, selecting patients for epidural LOA based on demographic and clinical factors may help better select treatment candidates. Procedural factors such as the use of hyaluronidase that increase risks and costs did not improve outcomes, so further research is needed before these become standard practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…A large retrospective, epidemiological study conducted in patients with radicular pain evaluated at Mayo Clinic found that although recurrence was frequent (31.7%), at the mean follow-up of 5.9 years, 90.5% of patients experienced either no or only mild pain. 28 The finding that higher pain scores and radicular symptoms are associated with chronicity and poor outcome for neck pain is similar to what occurs with low back pain [29][30][31][32] and suggests that both subjective and objective factors play a role in prognosis.…”
Section: Natural Course Of Neck Painmentioning
confidence: 85%
“…A large retrospective, epidemiological study conducted in patients with radicular pain evaluated at Mayo Clinic found that although recurrence was frequent (31.7%), at the mean follow-up of 5.9 years, 90.5% of patients experienced either no or only mild pain. 28 The finding that higher pain scores and radicular symptoms are associated with chronicity and poor outcome for neck pain is similar to what occurs with low back pain [29][30][31][32] and suggests that both subjective and objective factors play a role in prognosis.…”
Section: Natural Course Of Neck Painmentioning
confidence: 85%
“…Yet, few studies have examined the factors associated with outcomes of epidural LOA. In a large retrospective analysis by Hsu et al conducted in 115 patients who underwent epidural LOA, the one variable that was most consistently associated with successful response in both univariate and multivariate analysis was age greater than 81 years [62]. A numeric rating score (NRS) <9 was also associated with a positive outcome.…”
Section: Factors Associated With Treatment Outcomementioning
confidence: 99%
“…However, in two other studies [42,43], the injectate volume was kept constant and a significant difference between catheter adhesiolysis and a control, high-volume ESI was reported, suggesting a benefit related to either the use of a catheter, hypertonic saline or both interventions. The beneficial effect volume confers is likely constrained by a ceiling effect, as Hsu et al found no differences in mean volumes injected in those subjects who experienced a positive results (mean 20.8 ml) and those with a negative outcome (20.2 ml) (Table 2) [62]. …”
Section: Factors Associated With Treatment Outcomementioning
confidence: 99%
“…Hsu et al 26 retrospectively studied 115 patients who underwent epidural lysis of adhesions for FBSS or spinal stenosis and reported a modest success rate. Thereafter, Ko et al 27 found that recurrence of pain within 2-4 weeks after selective nerve root block can be reduced when hyaluronidase is added to the routine block regimen.…”
Section: Resultsmentioning
confidence: 99%